PENGEMBANGAN POLA PEMBELAJARAN AGAMA BERBASIS HUMANIS DI MADRASAH - Sulalah, Sulalah (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2008)
Members of a religious community have naturally strereotypical opinion about those of religious communities. It is a universal thing in the interaction amongst religions of the education people, with complexity gap from the past up to now not yet filled by strategic concepts in an attempt to buil, mutual respect, harmony, and human ringh. Through his analytic study, the writer highlights` the needs for the govermments to strengthen the religious followers integration through the programs of the humanity education in Indonesia. Keyword: Religious Community, Humanism, Teaching